Pre-Service Elementary Teachers’ Attitudes and Utilisation of Artificial Intelligence in Academic Activities - Femi, Iliasu Samuel; Sulaimon, Jamiu Temitope; Kolawole, Joshua; Wijayanti, Palupi Sri (Universitas Muhammadiyah Surakarta, 2025)
Artificial intelligence (AI) is transforming education rapidly. However, awareness of AI and its utilization varies significantly across professional fields and educational levels. This study investigated pre-service teachers' attitudes towards and use of AI in teaching and learning activities in Nigeria. A descriptive survey method was employed involving 96 pre-service teachers from a private college of education in Kwara State who were selected via simple random sampling. Data were collected using the Pre-service Elementary Teachers' Attitudes and Utilization of Artificial Intelligence in Teaching-Learning Activities Questionnaire (PSETAUAIQ), which demonstrated strong reliability (index = 0.77). The findings were insightful: Pre-service teachers consistently expressed positive attitudes towards integrating AI into their teaching, and the study revealed a high level of AI utilization among them. Crucially, analysis confirmed no significant difference in attitudes or AI utilization based on gender. Based on these results, it is strongly recommended that pre-service teachers receive comprehensive ethical training to ensure the responsible and effective use of AI tools in their future classrooms.